The Effect of Special Skill exercises on Accuracy and Some Bio - kinematical Variables in Low and High Setting for Youth Setters Baghdad Volleyball Clubs - Abbas, Ammar Waleed; yasser, Alaa mohsin (Journal of Physical Education, 2021)
The study aimed at identifying the effect of some special skill exercises on some bio- kinematical variables and the accuracy of low and high jump setting in volleyball. The subjects were (29) youth setters from Baghdad clubs only (5) setters were selected from Al Senaa, Al Shorta, Al Huria, Al Selaik, and the specialized schools for gifted in Baghdad. The researchers used the experimental method and the main experiment included taping the subject with (240 pix/se) camera to extract bio- kinematical variables. The special skill exercises were applied for two months followed by posttests. The data was analyzed using (Kinovea) then statistically using SPSS. The results showed significance in favor of posttests. Finally the recommended the necessity of using special skill exercises due to their great effect on setting kinematics that develops the motor pathways of setting.